1983/84 ショウワ キチ シュウヘン テイチャク ヒョウカ ノ クロロフィル α ゲンゾン リョウ ト カンキョウ ジョウケン ノ キセツ ヘンカ - 佐藤, 博雄; サトウ, ヒロオ; 渡辺, 研太郎; ワタナベ, ケンタロウ; 神田, 啓史; カンダ, ヒロシ; 高橋, 永治; タカハシ, エイジ; Satoh, Hiroo; Watanabe, Kentaro; Kanda, Hiroshi; Takahashi, Eiji (1986)
P(論文) 昭和基地周辺定着氷下のクロロフィルαと水温, 塩分などの海洋環境条件を測定した。1983年2月から1984年1月の間, 水温および塩分はそれぞれ-0.94--2.11℃, 32.42-34.70の範囲であった。この年の特徴として, 5月に海氷が流失し, 6月に表層から深層まで均質の水となり, 7月下旬には過冷却水が表層付近に見られた。この現象は1982年の状況と異なっていた。クロロフィルα濃度は1月から2月の間に最大となり, 3月中旬には減少した。その濃度は6月から10月までは0.1mg chl.α/m^3以下であり, 12月初旬に再び増加する傾向が見られた。1984年1月中旬に測定されたクロロフィルαの水柱積算量は1983年の同じ時期の量の半分以下であった。この低い現存量は, 1983年10月から1984年1月にかけての積雪に起因して, 水中の光量が少なかったためと推測される。 Phytoplankton pigments and oceanographic parameters were measured in water column under the fast ice near Syowa Station (69°00'S, 39°35'E) from February 1983 to January 1984. Water temperature and practical salinity ranged from -0.94 to -2.11℃ and from 32.42 to 34.70,respectively. After the flowout of sea ice in May 1983,very unusual event in recent years, the water column was mixed vertically in June, and then supercooled surface water beneath the newly formed ice appeared in late July, which differed remarkably from the phenomena in the preceding year. In this study, maximum chlorophyll α concentration of 4.99mg/m^3 was recorded in middle February 1983,and it descreased in middle March. The winter minimum less than 0.1mg chl.α/m^3 was observed from June to October, and the concentration increased again after early December. The standing stocks of chlorophyll α in middle January of the present year (1984) were less than half of those in the preceding year (1983). This could be explained by smaller light penetration into the underlying water between spring and summer of 1983/84 probably due to thicker snow cover on the sea ice comparing to that in 1982/83. departmental bulletin paper